1996
DOI: 10.1007/bf00170108
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the aquatic hyphomycetes of a sulfur spring in the Western Ghats, India

Abstract: Studies on the occurrence of aquatic hyphomycetes were carried out in Panekal sulfur spring in the Western Ghats, India by incubation of leaf litter and analysis of natural foam and of induced foam. Sampling was done once every three months over a period of two years from September 1989 to June 1991. The temperature, pH, dissolved oxygen, and sulfide content of water were also measured. No fungi were observed within the spring, whereas 16 species belonging to 13 genera were isolated from two outflow sites of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…In particular, through relevant research of 147 genera of fungi, it was found that 14 genera of fungi were detected for the first time in the coastal environment, among which the abundance of 2 genera— Laetisaria [ 26 ] and Spirosphaera [ 27 ]—ranked in the top 10 of all fungi. The remaining 12 fungal genera were as follows: Gibellulopsis [ 28 ], Monacrosporium [ 29 ], Spegazzinia [ 30 ], Rhizopycnis [ 31 ], Dokmaia [ 32 ], Vermispora [ 33 ], Hirsutella [ 34 ], Erythricium [ 35 ], Limonomyces [ 36 ], Entorrhiza [ 37 ], Dinemasporium [ 38 ], and Villosiclava [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, through relevant research of 147 genera of fungi, it was found that 14 genera of fungi were detected for the first time in the coastal environment, among which the abundance of 2 genera— Laetisaria [ 26 ] and Spirosphaera [ 27 ]—ranked in the top 10 of all fungi. The remaining 12 fungal genera were as follows: Gibellulopsis [ 28 ], Monacrosporium [ 29 ], Spegazzinia [ 30 ], Rhizopycnis [ 31 ], Dokmaia [ 32 ], Vermispora [ 33 ], Hirsutella [ 34 ], Erythricium [ 35 ], Limonomyces [ 36 ], Entorrhiza [ 37 ], Dinemasporium [ 38 ], and Villosiclava [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the published works from 2015-2020, 40 novel pleosporolean taxa were discovered: Aigialaceae (1 species) [93], Anteagloniaceae (1 species) [14], Astrosphaeriellaceae (2 species) [14], Dictyosporiaceae (7 species) [14,[94][95][96][97], Latoruaceae (2 species) [14,98], Lentitheciaceae (4 species) [20,99,100], Ligninsphaeriaceae (1 species) [15], Lindgomycetaceae (3 species) [14,101], Longipedicellataceae (3 species) [14], Lophiostomataceae (1 species) [14], Melanommataceae (1 species) [97], Morosphaeriaceae (3 species) [14,102], Nigrogranaceae (1 species) [14], Occultibambusaceae (1 species) [103], Parabambusicolaceae (1 species) [14], Phaeosphaeriaceae (1 species) [104], Pleosporales genera insertae sedis (2 species) [11,14], Pseudoastrosphaeriellaceae (1 species) [14], Tetraplosphaeriaceae (1 species) [14], Trematosphaeriaceae (1 species) [97], and Wicklowiaceae (2 species) [19,24]. Camposporium thailandicum is an addition to the known twelve Camposporium species recorded in freshwater habitats: C. antennatum [105][106][107], C. appendiculatum [27], C. cambrense [108][109][110], C. fusisporum [111], C. h...…”
Section: Discussionmentioning
confidence: 99%
“…Nueve especies se registran por primera vez en el estado de Tabasco y México. Además, se encontraron dos especies previamente identificadas tanto en ambientes dulceacuícolas como asociadas a restos vegetales: Phalangispora nawawi, encontrada en ambientes dulceacuícolas en Venezuela (Smits et al, 2007;Fernández et al, 2010;Fernández y Smits, 2015), y que en México fue registrada en restos vegetales en el estado de Veracruz (Heredia et al, 2000); mientras que Wiesneriomyces laurinus se ha reportado en ambientes dulceacuícolas de Brasil (Schoenlein-Crusius y Piccolo, 2003), Cuba (Delgado-Rodríguez y Mena-Portales, 2004), India (Rajashektar y Kaveriappa, 1996Kaveriappa, y 2003Sudheep y Sridhar, 2011), Japón (Hoyosa y Tanaka, 2007), y en México, en restos vegetales en Veracruz (Heredia et al, 2000)y Tabasco (Becerra et al, 2007;Martínez-Rivera et al, 2014).…”
Section: Discussionunclassified